Deleuze and anarchism - Van Heerden, Chantelle; Eloff, Aragorn (Deleuze connections., 2020)
This collection of 13 essays addresses and explores Deleuze and Guattari's relationship to the notion of anarchism: in the diverse ways that they conceived of and referred to it throughout their work, and also expands it in terms of the spirit of their philosophy and in their critique of capitalism and the state.